Territorial Imperatives of Industrial Production Development - KISELEVA, Natalia Nikolaevna; ORLYANSKAYA, Anna Aleksandrovna; TLISOV, Azamat Borisovich; TATUEV, Arsen Azidovich; GUKASOVA, Nina Rafaelovna (Journal of Advanced Research in Law and Economics; Vol 8 No 2 (2017): Volume VII, Issue 2(24), Spring 2017, 2017)
Global development challenges of the Russian economy emphasize imperative character of the problem solution of united economic space of the country for economic growth and development. The research of functioning regularities and territorial economic system development is one of dynamically developing directions of the modern science. In this paper, the paradigms of territorial production arrangement which developed in the Russian and western economic science are considered. The interaction directions of the Russian and western economic science are described. The key factors influencing territorial arrangement of the industry in modern conditions are described.